HUBUNGAN ANTARA LEADER MEMBER EXCHANGE DAN PSYCHOLOGICAL CAPITAL PADA PERAWAT RUMAH SAKIT JIWA - SAPUTRI, INTAN ALVI WAHYU; Prihatsanti, Unika (Empati, 2017)
Hospitals can provide maximum service if the psychological condition of the nurse is positive. Psychological capital is a positive attitude in the nurse characterized by hope, self-efficacy, resilience, and optimism. Leaders who implement leader member exchange will have a positive interaction with their members. This study aims to determine the relationship between leader member exchange with pychological capital in mental hospital nurses. The population of this study is nurses RSJD Dr. Amino Gondohutomo. The sample of 70 nurses selected using cluster random sampling technique. Data collection uses two scales: psychological capital scale (42 valid items, Î± = .960) and leader exchange member scale (26 valid items, Î± = .919). The result shows correlation coefficient (rxy) = .800 with p = value (p <.001). These results indicate that the hypothesis proposed by the researcher is proved, that there is a significant positive relationship between variable of leader member exchange with psychological capital. The more positive the leader member exchange the higher the psychological capital. The effective contribution given in this study in amount of 64% and 36% affected by other factors not measured in this study.Â Â